The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00264-013-1996-0
|View full text |Cite
|
Sign up to set email alerts
|

Does computer-assisted total knee arthroplasty improve the overall component position and patient function?

Abstract: Purpose There remains controversy as to whether computernavigated total knee replacement (TKR) improves the overall prosthesis alignment and patient function. The aim of this study was to determine whether computer-assisted total knee arthroplasty provides superior prosthesis positioning when compared to a conventional jig-assisted total knee replacement and whether this affected the functional outcome. Methods This prospective, randomised controlled study compared computer navigated and conventional jig-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
20
0
1
Order By: Relevance
“…Earlier lack of evidence on post-operative functional improvement has been one of the reasons CAOS did not gain so much popularity. Some studies found no difference in functional outcome between CAOS group and traditional group [ 27 , 28 ]. Outcome assessment factors are gross and not powered enough to detect the statistical difference in most small studies.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier lack of evidence on post-operative functional improvement has been one of the reasons CAOS did not gain so much popularity. Some studies found no difference in functional outcome between CAOS group and traditional group [ 27 , 28 ]. Outcome assessment factors are gross and not powered enough to detect the statistical difference in most small studies.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the use of computer navigated arthroplasty instead of surgeons using simple templates and jigs failed to show any improvement in the literature [ 126 ]. A new development in arthroplasty is the use of patient specific TJR where components are produced to precisely match a preoperative MRI scan of the patient's joint.…”
Section: Joint Registry Datamentioning
confidence: 99%
“…In another systematic review, improved coronal plane alignment with fewer radiographic outliers was described but function was not improved [22]. Several other authors have reported no significant advantage in functional outcome at 2-and 5-year follow-up for computer-navigated technique over conventional jig-based technique [23][24][25][26][27]. Despite the positive potential for similar accurate results achieved by novice and experienced users in one study [28], some authors have reported general increased surgical time with navigation-assisted TKR [14,21,22].…”
Section: Discussionmentioning
confidence: 99%